lmpact of reafforestation with Eucalyptus globulus La bi l l . on the edaphic collembolan fauna of Serra de Monchique ( Algarve , Portugal ) - Barrocas, H M; Gama, M M; Sousa, J P; Ferreira, C S (Miscel.lania Zoologica, 1998)
lmpact of reafforestation with Eucalyptus globulus Labill. on the edaphic collembolan fauna of Serra de Monchique (Algarve, Portugal).- Native forests in Portugal have been gradually replaced by Eucalyptus globulus plantations. This exotic tree has been referred as a major factor of ecosystem disturbance (Gama et al. 1989, 1991, 1994, 1995; Sousa & Gama, 1994; Vasconcelos et al., 1994). The authors compared edaphic Collembola populations occurring in coppices of Quercussuber L. and Q. canariensis Willd. with those from stands of Eucalyptusglobulus Labill. from Serra de Monchique, to evaluate the effects of reafforestation with this exotic tree. The total analysis of data shows a rupture in the collembola communities associated with eucalyptus. Oak biotopes usually present higher values of diversity and species richness, with a greater total number of species and also more exclusive andlor preferential species than eucalyptus biotopes. No significant differences were detected among the different biotopes in terms of mean number of individuals. However, the abundance of individuals in eucalyptus biotopes results mainly from the presence of a few species which are represented by a great number of specimens, making up more than 85% of the individuals on eucalyptus sites
Keywords: Algarve; Collembola; Eucalyptus globulus; Q. canariensis; Quercus suber; REAFFORESTATION